2006
DOI: 10.5194/acp-6-769-2006
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance measurements and parameterisation of traffic related particle emissions in an urban environment

Abstract: Abstract. Urban aerosol sources are important due to the health effects of particles and their potential impact on climate. Our aim has been to quantify and parameterise the urban aerosol source number flux F (particles m −2 s −1 ), in order to help improve how this source is represented in air quality and climate models. We applied an aerosol eddy covariance flux system 118.0 m above the city of Stockholm. This allowed us to measure the aerosol number flux for particles with diameters >11 nm. Upward source fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
79
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 24 publications
16
79
0
Order By: Relevance
“…While frequently applied to CO 2 and other gas phase species, the application of the eddy covariance approach to aerosols has been limited by the stringent instrumental requirements: measurements must not only be portable and free of interference, but they must also be fast and sensitive enough to capture fluctuations on the time scale of flux-carrying turbulent eddies (≥5 Hz). Fluxes of total or size-resolved aerosol number (without chemical information) have been performed for some time (e.g., Katen et al, 1985;Sievering, 1987;Buzorius et al, 1998;Dorsey et al, 2002;Mårtensson et al, 2006;Vong et al, 2010). However, total and chemically-resolved particle mass fluxes have lagged behind because most instruments measuring mass or aerosol chemical composition are far from meeting the rigorous requirements for EC, and most chemically-resolved aerosol flux measurements have been indirect with slower time resolution approaches (e.g., Nemitz et al, 2004b;Trebs et al, 2006;Myles et al, 2007;Thomas et al, 2009;Wolff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While frequently applied to CO 2 and other gas phase species, the application of the eddy covariance approach to aerosols has been limited by the stringent instrumental requirements: measurements must not only be portable and free of interference, but they must also be fast and sensitive enough to capture fluctuations on the time scale of flux-carrying turbulent eddies (≥5 Hz). Fluxes of total or size-resolved aerosol number (without chemical information) have been performed for some time (e.g., Katen et al, 1985;Sievering, 1987;Buzorius et al, 1998;Dorsey et al, 2002;Mårtensson et al, 2006;Vong et al, 2010). However, total and chemically-resolved particle mass fluxes have lagged behind because most instruments measuring mass or aerosol chemical composition are far from meeting the rigorous requirements for EC, and most chemically-resolved aerosol flux measurements have been indirect with slower time resolution approaches (e.g., Nemitz et al, 2004b;Trebs et al, 2006;Myles et al, 2007;Thomas et al, 2009;Wolff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that small aerosol particles followed the same laws of turbulent motion as air molecules, that is, the fluctuation of the particle concentration followed the "−5/3" power law under unstable atmospheric stratification, and the concentration-velocity co-spectra for particle number flux followed the "−4/3" power law (Mårtensson et al, 2006;Vogt et al, 2011a;Kaimal et al, 1972). Therefore, the distribution of small particles can be regarded as a passive conservative quantity, just like the temperature field.…”
Section: Theory Of Aerosol Mass Flux Measurementmentioning
confidence: 99%
“…The sonic anemometer measurements showed that the turbulence characteristics over the campus did not exhibit significant inhomogeneity. The measurement height of 18 m above the reference plane was high enough to meet the isotropy assumption (Mårtensson et al, 2006).…”
Section: Measurement and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The site has been previously described by Mårtensson et al (2006) and Vogt et al (2011a,b,c Identical aethalometers series 8100 (Magee Scientific, USA) were used to obtain BC concentrations on Hornsgatan (3.5 m above ground in the street canyon) and Torkel Knutssonsgatan (roof top). These instruments were operated with PM 2.5 sample inlets and a sample flow rate of 2 L min −1 .…”
Section: Sampling Sitesmentioning
confidence: 99%